Kajian Teologis Terhadap Penerapan Tradisi Masseroi Tondok Dalam Budaya Seko Di Desa Malimongan, Kecamatan Seko - Selan, Yunus; Hasmi, Hasmi; Manu, Charisal B.S.; Sahari, Gunar; Harti, Sri Dwi; Basongan, Citraningsih (JURNAL LUXNOS, 2025)
This research examines the application of the Masseroi Tondok tradition in the culture of the Seko community in Malimongan Village, Seko District, through a theological approach. Masseroi Tondok, which means "cleaning or organizing the village", is a traditional tradition that contains strong spiritual and social values. The main aim of this research is to explore the theological meaning contained in the implementation of this tradition and its implications for the religious and cultural life of the local community. The method used is descriptive qualitative with a contextual theological approach, through in-depth interviews, participatory observation and literature study. The results of the study show that the Masseroi Tondok tradition not only functions as a traditional ritual, but also reflects divine values, such as gratitude, purity and harmony with nature and fellow humans. This tradition also strengthens cultural identity and builds social solidarity of the Seko community. These findings indicate that there is close integration between theological values ​​and local wisdom in the cultural practices of the Seko community.